Tempos de lutas e esperanças: a materialização da revista Seiva (1938-1943) - Ferreira, Daniela de Jesus (2012)
The survival of the Regional Committee of the Communist Party of Bahia after the strong repression of the Brazilian state in 1935 contributed to some communist Bahia followed by the path of letters through the articulation and production of a magazine. The magazine was called Seiva, and became the first newspaper circulating in the anti-fascist Estado Novo scenario. To circumvent the censorship which prohibited and investigated any and all opposition to the government, the Journal had the characteristic literary principle. Produced 18 editions along its "first phase", which lasted from 1938 to 1943, when was prohibited by Government of Getulio Vargas . Analyzed the Seiva as an instrument of action and fight the Bahians Communists in Brazilian society. They were articulate and aware of the role they played for the Party and the behavior that intellectuals should meet intervening in reality, opining and talking about racial issues and social inequalities that affected Brazil and Latin America.